A New Karaite-Turkish Manuscript from Germany: New Light on Genre and Language in Karaite and Rabbanite Turkic Bible Translations in the Crimea, Constantinople and Elsewhere - Shapira, Dan (Karaite Archives, 2014)
A Karaite manuscript in Istanbuli Turkish written in Hebrew characters has turned up in Germany lately. This article investigates the whereabouts of the manuscript and tries to place it in its historical and linguistic context. Although the manuscript was apparently written/copied in Constantinople, the Turkic language used in it has some Crimean connections. The novelty of this discovery lies in the fact that Turkish was used by the 19th century Constantinople Karaites as a literary language.